Decitabine combined with low dose idarubicin and cytarabine (D-IA) followed by allo-HSCT improves acute myeloid leukemia and higher-risk myelodysplastic syndrome patient outcomes: results from a retrospective study. Issue 8 (3rd July 2021) - Xu, Weilai; Ye, Li; Mei, Chen; Zhou, Xin-ping; Ren, Yanling; Ma, Liya; Ye, Xinnong; Lu, Chenxi; Jin, Jie; Tong, Hong-yan
Abstract: Treatment for acute myeloid leukemia (AML) and high-risk myelodysplastic syndrome (MDS) ineligible for intensive chemotherapy is a major challenge for clinicians. We enrolled 154 patients ineligible for intensive chemotherapy who were prescribed D-IA regimen (decitabine 15–20 mg/m 2 days 1 to 3–5, followed by idarubicin 3 mg/m 2 for 5–7 days and cytarabine 30 mg/m 2 for 7–14 days). For AML and MDS patients, the overall response rate after two cycles was 66.4% and 76.6%, respectively, and the 2-year overall survival rates were 29% and 31%, respectively. Fourteen (13.1%) AML and five (10.6%) MDS patients underwent allo-HSCT after complete remission. The allo-HSCT group survival time was significantly longer than the control group (median survival time not reached in HSCT group, 13 and 18.5 months in non-HSCT AML and MDS group). We concluded that D-IA regimen was effective and well tolerated for patients with AML or higher-risk MDS ineligible for intensive chemotherapy.